Pertimbangan Mubah Dan Haram Pembuatan Karya Tulis Penggemar Merujuk Pasal 9 UU Hak Cipta - Azwa Khaliza; Tajul Arifin (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Fan writing according to the Copyright Law is included in adaptation works referring to Article 40 Paragraph (1) of the Copyright Law as one of the protected works. The lack of legal rules regarding adaptation works in particular has led to the rampant commercialization of fan-written works whose legality and licensing rules are not in accordance with the rules. Referring to Article 9 of the Copyright Law, a person who obtains economic rights for publishing and adapting works must have obtained permission from the creator or copyright holder. Both the publisher and the author bear the consequences in this case of not obtaining permission and have taken exclusive rights, which consist of economic rights and moral rights bound to the original creation. The consideration between permissible and haram in the creation of this work depends on whether the publishing and commercialization of the written work causes profit or harm to the original character. It can be said to be permissible if the work does not get the permission of the original character but is also not published and not commercialized, so that the author does not get any benefit. Meanwhile, it can be said to be haram, according to Abu Dhar's Hadith on the Prohibition of Doing Harm, if publishing and reproducing a work is an act of exceeding the limit because it has taken the owner's rights without permission. Therefore, it can be considered haram because it is tantamount to seizing other people's property.